Usulan desain Arsitektur Enterprise untuk Agroforestry dan Ecotourism menuju Industry 4.0 - Daniel Avian Karjadi; Erick Dazki; Richardus Eko Indrajit (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Management of forest resources can generate income for individuals or companies including agroforestry and ecotourism. In times of a pandemic like recent times, the application of technology with the Industry 4.0 framework is needed the most and is no longer a privilege. However, the implementation of Industry 4.0 technology requires large investment or cost so that a collaborative ecosystem is required from several stakeholders such as forest planter, crop planters, livestock and ecotourism business actors with suppliers, customers and policy makers. In its application, even for Information Technology (IT) system in general, the use of Enterprise Architecture is a mediator between business language and IT language. With all of that background and a literature study approach, this research will propose an Enterprise Architecture design with an Industry 4.0 framework in the agroforestry industry and ecotourism that can be used together to form an integrated ecosystem from various stakeholders, both for companies of various scales and small farmers if supported by the government or a larger company for better efficiency and common interests.